Feeding Practices and Care-Seeking Behaviours among Mothers of Under-Two Children with Diarrhoeal Diseases in Bangladesh - Begum, Rowshan Ara; Akter, Jesmin; Kabir, Iqbal; Persson, Lars-Ake (International Journal of Child Health and Nutrition, 2013)
In Bangladesh, the prevalence of diarrhoea is the highest among children aged 6-23 months and the outbreaks are common among slum-dwellers of Dhaka city, Bangladesh. A qualitative explorative research was undertaken among slum-dwellers to explore the feeding practices and care-seeking behaviours of mothers with children with diarrhoeal diseases aged less than two years. Data were collected through in-depth interviews, focus-group discussions and observation checklist with mothers and elder family members. Breastmilk was blamed for causing diarrhoea among predominantly or exclusively breastfed children. The blameworthiness leads to withholding of breastfeeding during diarrhoeal episodes especially with recurrent and persistent diarrhoea. Teething, eating protein diet by children and eating leafy vegetables by mothers were believed to be responsible for diarrhoea among the older children. Hand-washing before preparing foods and before feeding children was virtually not practised. Usual complementary foods were not offered to the children with diarrhoea. Almost all of the children were offered oral rehydration salt solution and other fluids at home. A common healthcare-seeking behaviour of the mothers was to give medicines from local drug stores. Some mothers performed some rituals for the purification of their breastmilk. As the mother’s diet was believed to be responsible for the child’s diarrhoea, some foods, especially leafy-vegetables, some types of fish, and meat, were restricted to the mothers. The study concludes that perceptions of mothers regarding the causes of children’s diarrhoea direct to inappropriate feeding practices and care-seeking behaviours of under-two children with diarrhoeal diseases.